A Description and Evaluation of the Concussion Education Application HEADS UP Rocket Blades. Issue 1 (January 2019) - Daugherty, Jill; Miles, Isa; Sarmiento, Kelly; Sansone, Cristina; Kroshus, Emily; Bethea, Brittaney
Background . Concussions are responsible for numerous emergency department visits and hospitalizations among children annually. However, there remains a great deal of confusion about how to prevent and manage concussions in youth. To teach children aged 6 to 8 years about concussion safety, the Centers for Disease Control and Prevention (CDC) created a mobile gaming application called HEADS UP Rocket Blades. This report introduces the game and presents findings on its evaluation. Methods . The aim of the game is to teach children what a concussion is, its commons signs and symptoms, how to prevent one, and what to do if one occurs. An early version of the game went through two rounds of usability testing with children and parents to obtain initial impressions and make improvements. Results . The first round of usability testing focused on the mechanics of the game. Based on feedback from this session, CDC and the developers simplified the messaging and adjusted the game's level of difficulty. The second round focused on the gaming experience. The children indicated that they enjoyed playing, and nearly all were able to relay at least one learning objective. Conclusions . Parents and children rated Rocket Blades as a good learning tool and indicated that they would download it for personal use.